Rotational Surfaces in R 4 with New and - Aydin, Muhittin Evren; Lopez, Rafael (Int Electronic Journal Geometry, 2024)
In this paper, we give a new approach to the rotational minimal surfaces in 4 -dimensional Euclidean space l[8 4 . One type of these surfaces is obtained by the composition of two families of rotations in orthogonal planes. For these surfaces, we give a new parameterization. Using this parametrization, we find new examples of rotational minimal surfaces and rotational surfaces with zero Gaussian curvature.
Keywords: Rotational surface; minimal surface; Gauss curvature